Formulation and Antimicrobial Evaluation of A Novel Anti-Acne Herbal Hydrogel (International Journal of Ayurveda and Pharma Research, 2022)
Objective: The present study evaluates anti-microbial effect of hydrogel formulated with the extracts of some indigenous drugs against Propionibacterium acne.Material and Method: Procured Manjishtha (Rubia Cordifolia L.), Shalmali (Salmalia malabarica (DC. Schott & Endl) Schott & Endl.), Daruharidra (Berberis aristate DC), Aloe vera (Aloe barbadensis Miller), Yashthimadhu (Glycyrrhiza glabra L). Extracts of all drugs except Aloe vera were collected by hydroalcoholic extraction using the Soxhlet apparatus. Aqueous extract of Aloe vera was collected by drying method. Two types of hydrogels were prepared with the extracts of these drugs, one with 5% extract and the other with 10% extract. Propionibacterium acne strains were collected from CSIR-Imtech Chandigarh. Culturing of bacteria was done by using nutrient broth. Nutrient agar was used for preparing the culture media. The antibacterial efficacy of the hydrogels was evaluated by comparing them with standard gentamycin. Result: The prepared hydrogel showed an anti-bacterial effect, but it is comparatively less when compared with the standard gentamycin. Conclusion: The prepared gel has anti-microbial activity. 10% hyrdogel showed better results than 5% hydrogel.